Penerapan Sistem Economic Order Quantity (EOQ) pada UMKM MyPetHouse - Valencia; Haryanto, Hery (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
Abstract In an era where technology is developing rapidly, quite a few MSMEs experience difficulties in carrying out their operational activities. Inventory is one of the most important factors that can influence the operational performance of a business. Unmanaged inventory conditions will have a huge negative impact on a company. Therefore, inventory management is the most important aspect that must be monitored and evaluated regularly by the company. The data collection methods used in this activity are primary and secondary data collection methods. The output of this activity is the MyPetHouse MSME inventory management application, which is web-based. The results of the EOQ system design are expected to help MSMEs in supplying and managing inventory, where EOQ helps MSMEs determine the right amount of inventory supply to reduce costs that will be incurred.